Protein Kinase Inhibitor Peptide as a Tool to Specifically Inhibit Protein Kinase A - Liu, Chong; Ke, Ping; Zhang, Jingjing; Zhang, Xiaoying; Chen, Xiongwen (Frontiers in Physiology, 2020)
The protein kinase enzyme family plays a pivotal role in almost every aspect of cellular function, including cellular metabolism, division, proliferation, transcription, movement, and survival. Protein kinase A (PKA), whose activation is triggered by cyclic adenosine monophosphate (cAMP), is widely distributed in various systems and tissues throughout the body and highly related to pathogenesis and progression of various kinds of diseases. The inhibition of PKA activation is essential for the study of PKA functions. Protein kinase inhibitor peptide (PKI) is a potent, heat-stable, and specific PKA inhibitor. It has been demonstrated that PKI can block PKA-mediated phosphorylase activation. Since then, researchers have a lot of knowledge about PKI. PKI is considered to be the most effective and specific method to inhibit PKA and is widely used in related research. In this review, we will first introduce the knowledge on the activation of PKA and mechanisms related on the inhibitory effects of PKI on PKA. Then, we will compare PKI-mediated PKA inhibition vs. several popular methods of PKA inhibition.